2024
DOI: 10.1001/jamanetworkopen.2023.50050
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransport Protein 2 Inhibitors in Patients With Type 2 Diabetes and Acute Kidney Disease

Heng-Chih Pan,
Jui-Yi Chen,
Hsing-Yu Chen
et al.

Abstract: ImportanceSodium-glucose cotransport protein 2 inhibitors (SGLT-2is) have demonstrated associations with positive kidney-related and cardiovascular outcomes in patients with type 2 diabetes. However, the association of SGLT-2is with outcomes among patients with type 2 diabetes and acute kidney disease (AKD) remains unclear.ObjectiveTo examine the long-term associations of SGLT-2is with mortality, major adverse kidney events (MAKEs), and major adverse cardiovascular events (MACEs) in patients with type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…Similarly to what was reported in two other studies, SGLT2is seem to be safe, as they do not cause new AKI episodes ( Agarwal et al, 2022 ; Alkas et al, 2023 ). These relatively neutral effects contrast with the benefits reported by Pan et al (2024 ), where patients with diabetes who survived hospitalization with AKI and who were treated with SGLT2is in the first 90 days after being discharged had a reduction in cardiorenal events and death.…”
Section: Discussioncontrasting
confidence: 69%
“…Similarly to what was reported in two other studies, SGLT2is seem to be safe, as they do not cause new AKI episodes ( Agarwal et al, 2022 ; Alkas et al, 2023 ). These relatively neutral effects contrast with the benefits reported by Pan et al (2024 ), where patients with diabetes who survived hospitalization with AKI and who were treated with SGLT2is in the first 90 days after being discharged had a reduction in cardiorenal events and death.…”
Section: Discussioncontrasting
confidence: 69%
“…Isolated oliguria, even without an increase in sCr, is linked to higher mortality [ 45 ]. Despite efforts to enhance risk stratification for poor kidney outcomes using biomarkers like NGAL in oliguric patients [ 46 , 47 ], they did not surpass the predictive performance of sCr [ 48 ]. Distinctions in risk among episodes of oliguria were acknowledged, and NGAL successfully differentiated functional oliguria from AKI based on sCr criteria in a separate study [ 49 ].…”
Section: Acute Kidney Injury Subphenotypes: Predictive and Prognostic...mentioning
confidence: 99%
“…They can also include patients with comorbid conditions excluded from clinical trials, elderly patients, or patients on wide range of treatment regimens. Recently, a large cohort study demonstrated that SGLT2 was associated with mortality reduction and major adverse cardiovascular events among patients with type 2 diabetes and acute kidney disease [8].…”
Section: Introductionmentioning
confidence: 99%